Qualitative assessment of the tear film in young adults - I.M. Bezkorovaina; D.O. Nakonechnyi; A.O. Bezkorovaina (Ukrainian Society of Ophthalmologists, 2019)
Introduction. Studying the quality of the tear film in young adults, who are the most active users of digital devices, is of extreme interest in clinical practice. Purpose. To study the qualitative characteristics of the tear film of the eye in young adults. Materials and Methods. We examined 486 eyes of 243 people, aged from 18 to 30, on average (23 ± 0.56). The Ocular Surface Disease Index was determined and the tests were performed in each patient. In addition, interferometry, tear meniscus and Non-invasive break-up time measurements were performed using the SBM ICP Tearscope (Italy) and iPad Pro (the USA) devices. Results. The examinees, aged 18-30, had the decreased tear film thickness, characterized by a positive correlation between the interferometry data and the tear production tests. The low (category I), moderate (category II), and high (III category) probability of dry eye disease was found in 35% (168 eyes), 31% (152 eyes), and 13% (65 eyes) of the examined young adults, respectively. Conclusions. Dry eye disease is a common chronic condition affecting the ocular surface in 38-64% of young adults. The thickness of the tear film lipid layer was decreased to 15 and 30-80 nm in 64% of cases; the tear meniscus was decreased in 42% of cases; and the tear film break-up time reduced in 57% of cases. It was possible to estimate the probability of dry eye disease in 79% of cases.